Study of Using Thymbra spicata leaves to reduce the toxic immunosuppresive effect of aflatoxin in broilers: Hatem M. M. Al-Naemey, Nwal S. Ja`afar and Hassiba A. Omran - Al-Naemey, Hatem M. M. (The Iraqi Journal of Veterinary Medicine, 2008)
The present study performed to evaluate the impact of addition ofThymbra spicata leaves powder of aflatoxin contaminated ration inreduction of the aflatoxin immuno suppressive effect in the immuneresponse induced by Newcastle disease vaccine in broilers.The study conducted in three groups, The first group fed aflatoxin freeration, second group fed aflatoxin contaminated ration without anytreatment, while the third group fed aflatoxin contaminated rationsupplemented of 2% Thymbra spicata leaves powder.All chick groups were vaccinated twice with Newcastle disease vaccine(NDV) at 10 and 20 days of age. ELIZA test was carried out to estimate thehumeral immune response at 6, 19 and 31 days of age. Infection challengwere done at day 32 of age with velogenic ND strain (Z-2003).The results showed that the first group has high significante antibodies titerreach to 3239±249.3 at 19days of age and 10186+845.3 at 31 days of agewith significant level 0.01 and high protection ratio against challenge(100%)at 32 days of age, while the second group has the low antibodies titerreach to 2622.6±27.3 at 19 days of age and 5712.5±786.9at 31daysof ageand low protection ratio against challenge(66.67), the third group’santibodies titer and protection ratio lower than first group and higher thansecond group ,the titers are 3060±542.5 at 19 days of age and 5712.5±786.9at31 days of age while the protection ratio against challenge is 80% at 32days of age .The results showed the immuno suppressive effect of aflatoxin as in secondgroup and the role of Thymbra spicata leaves powder in reduction of theseeffect.